2005
DOI: 10.2174/1568014054546326
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptotic Cell Death in Tumor Cells by S100A8/A9 Released from Inflammatory Cells Upon Cellular Activation

Abstract: Polymorphonuclear neutrophils (PMNs) have received less attention than other leukocyte subsets as potential mediators of antitumor effects. However, there is a growing body of evidence that PMNs are potential mediators of antitumor effects and play an important role in the antitumor response. A protein complex S100A8/A9, formed by the two low molecular weight calcium-binding proteins S100A8 and S100A9, is released from activated PMNs and has apoptosis/cytotoxicity-inducing activity against tumor cell lines. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
(158 reference statements)
0
4
0
Order By: Relevance
“…It has been previously reported that treatment of HT29/249 and SW742 cells with S100A8/A9 increases the intracellular level of ROS, and antioxidants reversed the apoptosis-inducing activity of S100A8/A9 [1,42]. This prompted us to investigate the mitochondrial pathway in S100A8/A9-induced cell death using cellular models in which Bcl2 was over-expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that treatment of HT29/249 and SW742 cells with S100A8/A9 increases the intracellular level of ROS, and antioxidants reversed the apoptosis-inducing activity of S100A8/A9 [1,42]. This prompted us to investigate the mitochondrial pathway in S100A8/A9-induced cell death using cellular models in which Bcl2 was over-expressed.…”
Section: Discussionmentioning
confidence: 99%
“…S100A8/A9 positive cells, macrophages and polymorphonuclear leukocytes have been shown to accumulate along the invasive margin of a cancer [40]. Moreover, S100A8/A9 is released upon cellular activation [41] and induces apoptosis in malignant cells [1,42].…”
Section: Discussionmentioning
confidence: 99%
“…After systemic administration, toxic side effects were apparent such as the cytokine release syndrome, which is induced in particular by bsAbs containing an anti-CD3 specificity [72,104,150]. Recently there has been a shift towards recruitment of immune system elements and the subsequent induction of apoptosis in consequence of inflammatory processes directed against tumor-associated and TSA contemporarily with death receptors in high amounts [8,74,79]. Theoretically, there is a robust potential to use the death receptors such as Apo--1/Fas/CD95, CD40, CD30, TNF receptors, and TRAIL receptors, not only in cancer, but also in other diseases [43,89].…”
Section: Therapeutic Cell−selective Targeting Of Death Receptors Withmentioning
confidence: 99%
“…Survival of pathologic cells (for example cells which are precancerous, infected or those that could elicit autoimmune response) may contribute to cancer, inflammation and autoimmune diseases. On the other hand, removal of essential cells through excessive apoptosis contributes to the pathogenesis of some degenerative diseases [6][7][8] components is therefore, a useful therapeutic approach to counteract either unwanted survival or death of particular cells associated with certain human diseases [9][10][11]. Most apoptotic pathways converge on the proteolytic activation of members of a family of cysteine aspartyl-specific proteases, (caspases).…”
Section: Introductionmentioning
confidence: 99%